Assessing Investment Feasibility in Tegal City: A Strategic Perspective on Infectious Waste Handling - Arfinto, Erman Denny; Yektiningsih, Novie; Damayanti, Nadia (Universitas Negeri Semarang, 2023)
Based on simulation data from recapitulation of Health Facilities waste or medical B3 waste in Tegal City in 2022, it was recorded as 454 kg of medical B3 waste per day. Recap of data for Health Facilities in areas around Tegal City (Slawi, Brebes, Pekalongan, Pemalang and Batang) recorded 3,336 kg of B3 medical waste per day. This condition has the potential to cause environmental problems if not addressed. This research aims to provide an analysis of the feasibility of investment for handling medical waste. The study used secondary data sourced from the Tegal District Government Health Service and primary data collected through field observations. The research results show that the condition is suitable to continue. Investment funds required are IDR. 28 billion more. The financial feasibility results show an Internal Rate of Return (IRR) using a discount rate of 7.042%. Net Present Value (NPV), for considering the time value of money of 7.042% produces a positive value. The Investment Payback Period does not exceed the loan term. The feasibility results from economic and social environmental aspects also show that this waste management investment can be recommended for regional government implementation.